Antidepressant and Anxiolytic Effects of Medicinal Cannabis Use in an Observational Trial - Martin, Erin L.; Strickland, Justin C.; Schlienz, Nicolas J.; Munson, Joel; Jackson, Heather; Bonn-Miller, Marcel O.; Vandrey, Ryan (Frontiers in Psychiatry, 2021)
Background: Anxiety and depressive disorders are highly prevalent. Patients are increasingly using medicinal cannabis products to treat these disorders, but little is known about the effects of medicinal cannabis use on symptoms of anxiety and depression. The aim of the present observational study was to assess general health in medicinal cannabis users and non-using controls with anxiety and/or depression. Methods: Participants (368 Cannabis Users; 170 Controls) completed an online survey assessing anxiety and depressive symptoms, cannabis product use, sleep, quality of life, and comorbid chronic pain. Participants that completed this baseline survey were then invited to complete additional follow-up surveys at 3-month intervals. Baseline differences between Cannabis Users and Controls were assessed using independent-samples t-tests and generalized linear mixed effects models were used to assess the impact of initiating cannabis product use, sustained use, or discontinuation of use on anxiety and depressive symptoms at follow-up. Results: Medicinal cannabis use was associated with lower self-reported depression, but not anxiety, at baseline. Medicinal cannabis users also reported superior sleep, quality of life, and less pain on average. Initiation of medicinal cannabis during the follow-up period was associated with significantly decreased anxiety and depressive symptoms, an effect that was not observed in Controls that never initiated cannabis use. Conclusions: Medicinal cannabis use may reduce anxiety and depressive symptoms in clinically anxious and depressed populations. Future placebo-controlled studies are necessary to replicate these findings and to determine the route of administration, dose, and product formulation characteristics to optimize clinical outcomes.